2021
DOI: 10.3389/fevo.2021.789371
|View full text |Cite
|
Sign up to set email alerts
|

K+ Nutrition Exchange in the Serendipita-Arabidopsis Symbiosis: Study of the Fungal K+ Transporters Involved

Abstract: There is mounting evidence that the root-colonizing endosymbiotic fungus Serendipita indica improves plant growth. The beneficial effects have been observed when plants are growing in optimal conditions or under nutritionally deficient soils (e.g., phosphate poor soil) or exposed to stressful environmental conditions such as drought or salinity. However, until now its role in the nutrition of other plant essential macronutrient, such as K+, has not been fully clarified. Here, we study the role of the fungus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Potassium depletion in the shoot could trigger the induction of HAK5 in cbl7 , as multiple independent studies demonstrated that HAK5 is induced under K + starvation (Ahn et al, 2004 ; Armengaud et al, 2004 ; Gierth et al, 2005 ; Shin & Schachtman, 2004 ). A recent study demonstrated the induction of HAK5 in the host plant as a general consequence of the symbiotic interaction (Conchillo et al, 2021 ), which would also explain why we found HAK5 under the consistently induced genes in wild‐type plants (Figure 1 ). Furthermore, the latter study demonstrated that the inoculation of Arabidopsis with S. indica does not improve the K + nutrition of the host plant under K + limiting conditions.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Potassium depletion in the shoot could trigger the induction of HAK5 in cbl7 , as multiple independent studies demonstrated that HAK5 is induced under K + starvation (Ahn et al, 2004 ; Armengaud et al, 2004 ; Gierth et al, 2005 ; Shin & Schachtman, 2004 ). A recent study demonstrated the induction of HAK5 in the host plant as a general consequence of the symbiotic interaction (Conchillo et al, 2021 ), which would also explain why we found HAK5 under the consistently induced genes in wild‐type plants (Figure 1 ). Furthermore, the latter study demonstrated that the inoculation of Arabidopsis with S. indica does not improve the K + nutrition of the host plant under K + limiting conditions.…”
Section: Discussionsupporting
confidence: 63%
“…As shown in Figure 4 , the potassium content of the cbl7‐2 roots grown at 0 mM KCl was similar to that of the Col‐3 control plants. However, the previously described decrease in K + contents in response to the inoculation with S. indica (Conchillo et al, 2021 ) was only observed in control plants, but not in cbl7‐2 . Interestingly, the K + level in the shoots of cbl7‐2 plants was significantly lower than in the mock‐treated wild type, equal to the level observed for Col‐3 treated with the fungus.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…SiHAK1, SiTRK1, SiTRK2 and SiTOK1 . 31 Nonetheless, in the low K + condition P. indica did not promote the growth of Arabidopsis. Surprisingly, under the condition of K + deficiency, P. indica reduces overall K + accumulation in the host plant while improving its own growth by expressing its own K + transporter gene SiHAK1 .…”
Section: Introductionmentioning
confidence: 96%
“…P. indica alters multiple phytohormonal regulated pathways during colonization, e.g. jasmonate-regulated secondary metabolite, glucosinolate pathway during early stages of interaction, 31 rapid increase in auxin levels during early recognition of the host, which is important for reprogramming the root development, 33 - elevated level of auxins in Arabidopsis roots, 5 and P. indica itself also produces IAA in the liquid culture. 34 In a recent study, it has been elucidated that P. indica employs putrescine for plant’s growth promotion.…”
Section: Introductionmentioning
confidence: 99%